2014
DOI: 10.1007/s11239-014-1154-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CHADS2 and CHA2DS2-VASc scores with left atrial enlargement: a prospective cohort study of unselected atrial fibrillation patients

Abstract: Assessment of thromboembolic risk is crucial for proper management of atrial fibrillation (AF) patients. Currently used risk score base only on scarce clinical data and do not take into consideration parameters including echocardiographic findings. The aim of this study was to evaluate if left atrium (LA) enlargement is associated with higher thromboembolic risk assessed by CHADS2 and CHA2DS2-VASc scores in a cohort of unselected non-valvular AF patients. Data from 582 AF hospitalizations occurring between Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
2
20
0
2
Order By: Relevance
“…A study included 582 patients with AF showed that up to 86.2% of patients had increased LAD and proved that CHADS2 and CHA2DS2-VASc score increased with increased LAD. 12) At the same time, Kleemann, et al 7) found that LAD > 50 mm was an independent risk factor of LAT and dense SEC by following up NVAF patients with 0 or 1 points in CHADS2 score. Our study also proved that LAD was the independent risk factor for LAT/SEC and had the moderate predictive value for LAT/SEC (AUC 0.731 in male, AUC 0.743 in female).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study included 582 patients with AF showed that up to 86.2% of patients had increased LAD and proved that CHADS2 and CHA2DS2-VASc score increased with increased LAD. 12) At the same time, Kleemann, et al 7) found that LAD > 50 mm was an independent risk factor of LAT and dense SEC by following up NVAF patients with 0 or 1 points in CHADS2 score. Our study also proved that LAD was the independent risk factor for LAT/SEC and had the moderate predictive value for LAT/SEC (AUC 0.731 in male, AUC 0.743 in female).…”
Section: Discussionmentioning
confidence: 98%
“…7) By adding some additional risk factors to CHADS2 and CHA2DS2-VASc score, especially in patients who should have anticoagulant therapy but were ignored, the stroke risk in NVAF patients can be determined at an earlier stage. 8,9) Recently, some researches have showed that SUA and LAD were risk factors of LAT/SEC, 3,7,[10][11][12] so this study was aimed to explore the additional predictive value of SUA and LAD to CHADS2 and CHA2DS2-VASc score in NVAF patients. We then explored the influence from SUA and LAD of patients who are 0 or 1 point in CHADS2 or CHA2DS2-VASc score.…”
mentioning
confidence: 99%
“…In the present patients, the prescription rate of anticoagulants increased from 47. Given that, currently, catheter ablation, which requires periprocedural anticoagulation therapy, is indicated mainly for patients with neither severe left atrial enlargement, severe left ventricular dysfunction, nor severe pulmonary disease, 30,31 the patients undergoing catheter ablation inevitably tend to have low CHADS2 score, 32 and thus, the association between increased catheter ablation for NVAF and increasing anticoagulation use for low CHADS2 score is understandable. SUZUKI S et al…”
Section: Anti-thrombotic Medication Prescription Ratementioning
confidence: 99%
“…Был рассмотрен вопрос о возможности ис-пользования шкалы CHA 2 DS 2 VASc как средства вы-явления пациентов с высоким риском возникновения ФП с интермиттирующей или асимптомной формами [10]. Большее количество баллов по шкалам CHADS 2 и CHA 2 DS 2 VASc ассоциировано не только с высоким риском тромбоэмболических осложнений при ФП, но и с увеличением индекса левого предсердия [32]. Шкала CHA 2 DS 2 VASc обладает достаточной силой для прогнозирования риска развития фибрилляции пред-сердий в общей популяции, количество баллов по ней прямо пропорционально риску [33], в то же время остается открытым вопрос об использовании CHA 2 DS 2 VASc с этой целью в условиях ОКС.…”
Section: New-onset Atrial Fibrillation In Acs впервые возникшая фибриunclassified